The craft of tonal counterpoint - Benjamin, Thomas; Benjamin, Thomas; Bach, Johann Sebastian, 1685-1750. (New York : Routledge, 2003)
The Craft of Tonal Counterpoint is an introductory text to the analysis and composition of tonal counterpoint. Using examples from the music of J.S. Bach - the master of this style - the author takes students through a series of carefully graded, cumulative exercises that stress both analysis and writing. Benjamin covers chromaticism and fugal writing in exceptional detail. The exercises cover a wide range of formats, including error detection, linear pitch reduction, analysis and composition. The book also incorporates a 100-page anthology of scores, effective for analysis, in-cla.
Line and other elements of style -- Nonimitative two-voice writing -- Chromaticism in two voices -- Composition of binary dance forms -- Double (invertible) counterpoint -- Imitation, canon -- The two-voice invention -- Three-voice counterpoint I : texture, rhythm, harmony -- Three-voice counterpoint II : chromaticism, triple counterpoint, canon -- Fugue I -- Fugue II -- Four-voice counterpoint -- Variation forms -- Cantus firmus procedure : the chorale prelude.
Revised edition of: Counterpoint in the style of J.S. Bach. 1986.
"Anthology (all works are by J.S. Bach)": pages 296-297
Includes bibliographical references (page 295) and index.
Print version record.
eBooks on EBSCOhost
Keywords: Bach, Johann Sebastian, -- 1685-1750 -- Criticism and interpretation; Bach, Johann Sebastian, -- 1685-1750; Bach, Johann Sebastian -- 1685-1750; Bach, Johann Sebastian, -- 1685-1750.; Bach, Johann Sebastian; Counterpoint -- Textbooks; Musical analysis -- Music collections; Analyse musicale -- Anthologies; MUSIC -- Instruction & Study -- Theory; Counterpoint; Musical analysis; Kontrapunkt; Contraponto; Música -- Alemanha; Electronic books; Collections; Criticism, interpretation, etc; Textbooks; Textbooks